An exploration of providing mental health skills in a generic advanced clinical practice programme. (11th July 2019) - Chadwick, Angelina; Murphy, Neil
Abstract : Background: advanced clinical practitioners (ACPs) are expected to be competent in their holistic assessment and management of individuals, which includes those with both physical and mental health problems. A mental health component was introduced within a generic advanced practitioner programme to support the development of mental health skills required by advanced clinical practitioners in training (ACPiTs). Aims: this research investigated the efficacy of content specific to mental health within an MSc ACP generic programme. Methods: a single case study approach was adopted, which used a purposive sample of 10 ACPiTs to explore personal beliefs and experiences using semistructured interviews. Verbatim transcription was undertaken followed by content and thematic analysis. Findings: Themes emerged included communication skills, and increased competence and self-awareness. Conclusion: insights provided by the ACPiTs showed they recognised the value of mental health teaching and exposure within their training programme in advancing their knowledge and skillset and, ultimately, increasing confidence in their clinical practice.